Association Between Measures of Muscle Strength and Performance of Daily Activities in Patients with Knee Osteoarthritis - Arjan de Zwart; Joost Dekker; Simon Verberne; Leo D Roorda; Martin van der Esch; Willem F Lems; Marike van der Leeden (Journal of Rehabilitation Medicine, 2022)
Objectives: Most studies of knee osteoarthritis use isokinetic peak strength as a measure of muscle strength. However, estimated one-repetition maximum (1-RM) may have a stronger relationship than isokinetic peak strength with daily activities. The aim of this study was to test the following hypotheses: first, the estimated 1-RM is more strongly associated than isokinetic peak strength with daily activities; and secondly, the estimated 1-RM is most strongly associated with the 6-minute walk test (6MWT), followed by the Get Up and Go test (GUG test) and the stair-climb test. Methods: Data were used for 177 patients with knee osteoarthritis from a randomized controlled trial on improving muscle strength. The patients had a mean age of 67.6 ± 5.8 years. Isokinetic peak strength was measured using a dynamometer, 1-RM was estimated with the 10-RM test, and physical performance was measured with the 6-minute walk test (6MWT), get-up and go test (GUG) test and stair-climb test, at the start and end of 12 weeks of resistance training. Linear regression analyses provided standardized betas (β) that were comparable between the different associations between measures of muscle strength and daily activities. Results: Compared with the estimated 1-RM, isokinetic peak strength was more strongly associated with all performance-based measures. The associations between the estimated 1-RM and performance-based tests were not ranked in the order hypothesized (6MWT, GUG test, stair-climb test). Conclusion: Contrary to the first hypothesis, isokinetic peak strength showed stronger associations with all daily activities than did estimated 1-RM. In addition, the second hypothesis regarding the activity-specific pattern for the 1-RM with regards walking, chair rising and stair climbing measurements was not confirmed.